The Impact of Online Gambling Among Indonesian Teens and Technology - Budiman, Ramdani; Romadini, Nurul Ayu; Herwandi Aziz, Muhammad Ardhana; Pratama, Agasta Gumelar (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2022)
This research is motivated by the development of technological advances. With advances in technology there is an increase in the problem of crime using sophisticated modus operandi. This form of crime is Cyber ??Crime. One of the cases of cybercrime that is rife at this time is gambling via the internet. Article 27 paragraph (2) of Law Number 11 of 2008 concerning Information and Electronic Transactions regulates the prohibition of electronic gambling with a maximum imprisonment of 6 (six) years and/or a maximum fine of Rp. 1,000,000,000.00 (one billion rupiah). Online gambling is a game that is carried out using money as a bet with the terms of the game and the amount of the bet determined by online gamblers and using electronic media with internet access as an intermediary. Online gambling is a phenomenon that cannot be denied and is found in society, especially among teenagers. They consciously know that gambling is included in deviant behavior which is considered bad by some people and is prohibited by state law, but this does not cover their interest in participating in it. This study aims to describe the behavior of teenagers who are addicted to online gambling. This research is a type of qualitative research with data analysis techniques using qualitative analysis. The results explained that the behavior of adolescents who were addicted to online gambling showed the following characteristics: spending more time playing online gambling, decreasing physical activity and neglecting health, avoiding important life activities, decreasing socialization processes, finding it difficult to break the desire to play online gambling, ignoring work and personal obligations and mental illness.